2021
DOI: 10.3390/molecules26144327
|View full text |Cite
|
Sign up to set email alerts
|

A Potassium Based Fluorine Containing Bioactive Glass for Use as a Desensitizing Toothpaste

Abstract: Potassium releasing bioactive glasses (BAGs) may offer improved relief for dentine hypersensitivity compared to conventional sodium containing BAGs by releasing K+ ions for nerve desensitization and occluding dentinal tubules to prevent fluid flow within dentinal tubules. Potassium oxide was substituted for sodium oxide on a molar basis in a fluoride containing BAG used in toothpastes for treating dentine hypersensitivity. The BAG powders were then immersed in an artificial saliva at pH 7 and tris buffer and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Potassium-containing BGs have shown increased performance in dental applications due to the desensitization properties of K + . 165 For example, Na 2 O was fully replaced with K 2 O, on a weight basis, in the BioMinF composition (36)(37)(38)(39)(40) SiO 2 -(28-30)CaO-(22-24)Na 2 O-(4-6)P 2 O 5 -(1.5-3)CaF 2 to determine the improvement on dissolution rates, apatite forming ability, and the eventual suitability for dentin hypersensitivity treatment. Static dissolution studies showed nearly equivalent performance of both parent BioMinF and K-substituted BioMinF with similar dissolution rate, pH change, and precipitation of fluorapatite.…”
Section: Biomaterials Sciencementioning
confidence: 99%
See 1 more Smart Citation
“…Potassium-containing BGs have shown increased performance in dental applications due to the desensitization properties of K + . 165 For example, Na 2 O was fully replaced with K 2 O, on a weight basis, in the BioMinF composition (36)(37)(38)(39)(40) SiO 2 -(28-30)CaO-(22-24)Na 2 O-(4-6)P 2 O 5 -(1.5-3)CaF 2 to determine the improvement on dissolution rates, apatite forming ability, and the eventual suitability for dentin hypersensitivity treatment. Static dissolution studies showed nearly equivalent performance of both parent BioMinF and K-substituted BioMinF with similar dissolution rate, pH change, and precipitation of fluorapatite.…”
Section: Biomaterials Sciencementioning
confidence: 99%
“…Several further studies have been published showing that potassium-based compositions provide therapeutic effects through blocking nerves in dentin tubules while also aiding in dental restoration. 165,348 4.1.4 Rubidium 4.1.4.1 Biological activity. Rubidium has no known natural biological role.…”
Section: Review Biomaterials Sciencementioning
confidence: 99%